ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN POST PARTUM BLUES: Faktor Resiko POST PARTUM BLUES - Sandra Harianis; Nurul Indah Sari (LPPM Universitas Abdurrab, 2022)
Depression is a common disorder in women of childbearing age. Many women experience depressive symptoms during the postpartum period, ranging from mild postpartum blues to significant mood disorders such as postpartum depression and postpartum psychosis. The ‘postpartum blues‘ are extremely common, affecting 30-75% of new mothers. This form of postpartum mood change is self-limited and requires no specific treatment other than education and support. The aim of this study is to determine analysis risk factors incidence of postpartum blues in Perumnas Public Health Center of Rejang Lebong District. This study used the observational approach with a cross-sectional design. Samples in this study were 73 people used screening instrument of Edinburg Postnatal Depression Scale (EPDS). This study was conducted in Tembilahan Hulu and Gajah Mada Public Health Center in March-April 2021. Data obtained with instrument test and observation sheet. Data analysis used the Chi-Square test (X2. The results of the analysis showed that there was a correlation between postnatal health education provided by health workers (p=0.001, CI 3.225 – 50.404, OR 12.750) and family involvement in taking care of the baby (p=0.003, CI 2.020 – 32.594, OR 8.114) with the incidence of postpartum blues. Meanwhile, pregnancy plans (p=0.736) and delivery complications (p=0.969) based on statistical tests did not have a significant correlation. Social support, information and assistance from health workers are needed for mothers who experience the postpartum blues and screening for the postpartum blues is carried out before the mother is allowed to go home for postpartum care at home